ANALISIS PERBEDAAN KINERJA KEUANGAN PERUSAHAAN SEKTOR KEUANGAN YANG TERCATAT DI BEI SEBELUM DAN SELAMA PANDEMI COVID-19 - Septian Yudha Kusuma; Ardian Widiarto (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2022)
The purpose of this study was to analyze differences in the financial performance of financial sector companies listed on the Indonesia Stock Exchange (IDX) before and during the COVID-19 pandemic. The research method is descriptive quantitative analysis. The data used is financial sector financial report data for 2019 before the pandemic and 2020 during the pandemic. The financial performance variables used in this study are ROA, NPM, Liquidity, and Stock Price. The results showed that there were differences in financial performance as measured by ROA, NPM, and Stock Prices before and during the pandemic. Meanwhile, financial performance as measured by liquidity surprisingly did not difference before and during the pandemic. This study also examines the differences in the sub-sectors of insurance, banking, financial institutions, securities companies, and others. The results and implications are also discussed in this study